Globalisation, Migration, and the Future of Europe : Insiders and Outsiders. - Talani, Leila Simona (Taylor & Francis, 2011)
Showcasing an original, interdisciplinary approach, this text examines the effect of migration on the domestic politics of individual states and how they are eroding the distinctions between the domestic and foreign policy, the 'inside' and 'outside' components of politics and law.